2018
DOI: 10.26529/cepsj.547
|View full text |Cite
|
Sign up to set email alerts
|

Croatian Preschool Teachers’ Self-Perceived Competence in Managing the Challenging Behaviour of Children

Abstract: • Managing behaviour is a complex component of the teaching process and one that teachers consistently identify as an area of great concern. This study aimed to examine teachers' perceptions regarding their competence for managing the challenging behaviour of young children and to identify the factors that affect these beliefs. A total of 204 preschool teachers working in Kindergarten Rijeka, Croatia participated. Teachers completed an exploratory survey of self-perceptions of competence in managing the challe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Managing student behaviour changes (D2_9) seems to still be a challenge for teachers. It appears that this difficulty is not directly related to the experience gained [74], however, a more professional support/assistance supplemented by deeper knowledge of class management is believed to have an important role in the diminishment of these difficulties [75].…”
Section: Discussionmentioning
confidence: 99%
“…Managing student behaviour changes (D2_9) seems to still be a challenge for teachers. It appears that this difficulty is not directly related to the experience gained [74], however, a more professional support/assistance supplemented by deeper knowledge of class management is believed to have an important role in the diminishment of these difficulties [75].…”
Section: Discussionmentioning
confidence: 99%
“…Razmatrajući odnos između osobina ličnosti, samoprocijenjene kompetentnosti za rad s djecom s teškoćama u inkluzivnim skupinama i triju dimenzija profesionalnog sagorijevanja, utvrđene su očekivane povezanosti.Implementacija inkluzivne obrazovne politike povećava zahtjeve edukatorima u inkluzivnim okruženjima, a ne osigurava dostatnu educiranost u inicijalnom obrazovanju ni osiguranoj profesionalnoj podršci (40,41). When considering the correlation between the personality traits, the self-estimated competency for teaching children with disabilities in inclusive settings and the three dimensions of professional burnout, the expected connections were determined.…”
Section: Discussionunclassified
“…When considering the correlation between the personality traits, the self-estimated competency for teaching children with disabilities in inclusive settings and the three dimensions of professional burnout, the expected connections were determined. The implementation of an inclusive education policy increases the demands from educators in inclusive environments, but it does not ensure sufficient education through initial education, nor does it provide the necessary professional support (40,41). Of all the personality traits, neuroticism has shown to be significantly correlated to all the dimensions of professional burnout, and extraversion and agreeableness have shown to be negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study found that teachers' sense of self-efficacy can be influenced by the preparation that they receive when developing their skills and knowledge [8,9]. Therefore, this research further examined the influence of a teacher's professional learning on their self-efficacy.…”
Section: Introductionmentioning
confidence: 91%
“…Verbal persuasion refers to the realistic feedback from others. The extra verbal support from others such as colleagues, principals, parents, and trainers will help teachers face challenging student behaviour [9,19,20]. Yet, the input can either strengthen the beliefs of efficacy or diminish them [13].…”
Section: Verbal Persuasionmentioning
confidence: 99%